Dhikr As A Therapy to Deal With Anxiety in Pregnant Women: Dhikr As A Therapy to Deal With Anxiety in Pregnant Women - Ramadani, Salsabila; Qurratul A’yun, Ayu (Program Studi Tasawuf dan Psikoterapi, 2023)
Using dhikr as mediation or therapy is something that is very influential on pregnant women. Dhikr is considered to be able to help individuals in forming belief in Allah SWT. Doing dhikr is the same as relaxation or mediation therapy which emphasizes how to rest and relax through reducing psychological tension or stress. One of the factors that play a role in the anxiety of pregnant women is the ability to manage emotions. This research uses descriptive qualitative method through observation and interviews. The results of interviews and observations show that dhikr therapy can help reduce anxiety experienced by pregnant women.